2011
DOI: 10.1097/cej.0b013e3283481df3
|View full text |Cite
|
Sign up to set email alerts
|

The oral cancer knowledge of dentists in Northern Germany after educational intervention

Abstract: The objective of this study was to assess the knowledge about oral cancer, in particular about diagnostic items and risk factors, after educational intervention by means of a standardized survey. On the basis of the evaluation at baseline, an educational programme consisting of different approaches (for instance, oral presentations, poster, DVD and a brochure) was designed. In May 2009, the questionnaire 'Practices and opinions about oral cancer' focusing on the knowledge about diagnostic factors and risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Forty-one papers from 37 studies assessed knowledge about HPV and HNC [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] . Over half ( n = 23) were conducted in the USA [46] , [47] , [48] , [49] , [52] , [54] , [56] , [62] , [67] , [68] , [69] , [70] , [71] , [73] , [74] , [75] , [76] , [77] , [78] , [80] , [82] , [83] , [84] , [85] , with others from Germany ( n = 4)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-one papers from 37 studies assessed knowledge about HPV and HNC [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] . Over half ( n = 23) were conducted in the USA [46] , [47] , [48] , [49] , [52] , [54] , [56] , [62] , [67] , [68] , [69] , [70] , [71] , [73] , [74] , [75] , [76] , [77] , [78] , [80] , [82] , [83] , [84] , [85] , with others from Germany ( n = 4)…”
Section: Resultsmentioning
confidence: 99%
“…All were published between 2002 and 2015. Quantitative studies ( n = 40) [45] , [46] , [47] , [48] , [49] , [50] , [51] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] used survey-based data collection methods and one qualitative study collected data using focus groups [52] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have had similar results with the present study as developed in Germany, where it was found that 64% of dentists perform oral cancer examinations for young people, and 94% of them considered performing this examination for the elderly over 40 years as essential. However, only about 30 percent of them performed such screening examinations for their patients in the first session or the next session [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are several risk factors for oral cancer; some of the known ones are different kinds of tobacco, alcohol, inappropriate life style and nutritional habits, viruses and the sunlight (8) Many studies in the United States, Canada and Europe have evaluated the knowledge of dentists about oral cancer and concluded that there is still needed to improve the knowledge of dentists in detection and management of oral cancers (9,10,11). They also recommended to conduct more studies in order to estimate current knowledge of dentists and to include it in future educational courses (11,12).…”
Section: Advances In Bioscience and Clinical Medicinementioning
confidence: 99%